2019
DOI: 10.1038/s41467-019-09040-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in the central nervous system hinder bacterial clearance during pneumococcal meningitis

Abstract: Neutrophils are crucial mediators of host defense that are recruited to the central nervous system (CNS) in large numbers during acute bacterial meningitis caused by Streptococcus pneumoniae . Neutrophils release neutrophil extracellular traps (NETs) during infections to trap and kill bacteria. Intact NETs are fibrous structures composed of decondensed DNA and neutrophil-derived antimicrobial proteins. Here we show NETs in the cerebrospinal fluid (CSF) of patients with pneumococcal menin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 69 publications
4
103
0
1
Order By: Relevance
“…During pneumococcal meningitis, NETs in the central nervous system have been reported to hinder bacterial clearance. NETs were present in the CSF of patients with pneumococcal meningitis, but absent in other forms of meningitis with neutrophil influx in the CSF 53 . Pneumococci-induced NET formation in the CSF of infected rats could be cleared upon intravenous application of DNase I resulting in a disruption of NETs in the CSF followed by bacterial clearance, suggesting that NETs may contribute to pneumococcal meningitis pathogenesis in vivo 53 .…”
Section: Nets and Eets In Bacterial Infectionsmentioning
confidence: 93%
“…During pneumococcal meningitis, NETs in the central nervous system have been reported to hinder bacterial clearance. NETs were present in the CSF of patients with pneumococcal meningitis, but absent in other forms of meningitis with neutrophil influx in the CSF 53 . Pneumococci-induced NET formation in the CSF of infected rats could be cleared upon intravenous application of DNase I resulting in a disruption of NETs in the CSF followed by bacterial clearance, suggesting that NETs may contribute to pneumococcal meningitis pathogenesis in vivo 53 .…”
Section: Nets and Eets In Bacterial Infectionsmentioning
confidence: 93%
“…Shotgun proteomic analysis of the CSF from patients with meningitis confirmed the presence of NET-related proteins, such as MPO, NE, proteinase-3 (PR3), cathelicidin LL-37, MMP-9, heparin binding protein (HBP), neutrophil gelatinase-associated lipocalin (NGAL), and histones [66]. Mohanty et al also detected the presence of NETs in the CSF from rats with pneumococcal meningitis [66]. In order to shed light on the role of NETs in the pathogenesis of meningitis, these authors performed a set of experiments using a rat meningitis and an in vitro model, attempting to degrade NETs with DNase I.…”
Section: Cns Infectionsmentioning
confidence: 97%
“…Other authors observed intensive infiltration of neutrophils in leptomeningitis and intraparenchymal vasculitis [63][64][65]. Recent literature reports that NETs are formed in the CSF of patients with pneumococcal meningitis, but not in viral meningitis, CNS borreliosis and subarachnoid haemorrhage [65,66]. In vitro culture of human neutrophils with bacteria isolated from meningitis patients (S. pneumoniae, N. meningitidis, L. monocytogenes, S. aureus, E. coli, A. baumanii, S. oralis, S. capitis and S. epidermidis) revealed that all except L. monocytogenes induced NETs [66].…”
Section: Cns Infectionsmentioning
confidence: 99%
See 2 more Smart Citations